Brief Report: Hormonal Contraception Is Not Associated With Reduced ART Effectiveness Among Women Initiating ART. (1st May 2017) - Patel, Rena C.; Baeten, Jared M.; Heffron, Renee; Hong, Ting; Davis, Nicole L.; Nanda, Kavita; Coombs, Robert W.; Lingappa, Jairam R.; Bukusi, Elizabeth A.; Hurst, Stacey; Thomas, Katherine K.; Kourtis, Athena P.; et al.
Abstract : Background: To explore the association between concomitant hormonal contraceptive and antiretroviral therapy (ART) use and (1) plasma viral suppression and (2) genital HIV shedding among HIV-positive women initiating ART. Methods: We analyzed plasma viral load and genital viral RNA shedding from 1079 HIV-positive women initiating ART who were followed prospectively in 3 sub-Saharan African HIV prevention studies. Plasma and endocervical swab samples were collected every 6 months. Self-reported contraceptive use was categorized into injectable, implant, oral, or nonhormonal/no contraception. We used multivariate Cox regression to assess time to plasma viral suppression and logistic regression with generalized estimating equations to assess genital viral shedding for each contraceptive method. Results: At the time of ART initiation, there were 211 (20%) injectable, 69 (6%) implant, 50 (5%) oral, and 749 (69%) nonhormonal or no method users. Plasma viral suppression was high (90% by 6 months) and hormonal contraceptives did not diminish time to plasma viral suppression as compared to nonhormonal/no methods [adjusted hazard ratios: injectables 0.89 (95% confidence interval: 0.75 to 1.07), implants 0.91 (0.68 to 1.23), and oral methods 1.33 (1.06 to 1.66)]. Genital viral shedding was uncommon any time after ART initiation (only 9% of samples had detectable viral shedding) and hormonal contraceptives were not associated with an increased detection of genital viral shedding [adjusted odds ratios: injectables 1.07 (0.69 to 1.65), implants 0.67 (0.31 to 1.49), and oral methods 0.56 (0.19 to 1.69)]. Conclusions: The hormonal contraceptives assessed were not associated with reduced ART effectiveness among HIV-positive women initiating ART. HIV-positive women should continue to be offered contraceptive options, including hormonal ones that best meet their needs.